Politeness Strategies Of Directive Utterances Used ByStudents Of English Department Of Muhammadiyah University Of Surakarta In Microteaching Class - Reswari, Rini (2012)
This research is aimed at answering three problem statements, namely the intentions of directive utterances, the types of politeness strategies used in directive utterances, and the language forms of directive utterances. In collecting the data, the researcher uses recording, transcribing and documention method. To answer the problem statements, the researcher uses the directive utterances theory of Austin, the politeness strategy theory of Brown and Levinson, and the language forms theory of Kreidler. From the analysis, the researcher finds 224 data. The results of the analysis show that the intentions of directive utterances of commanding utterance is 131 data (58.48%), requesting utterance is 77 data (34.37%), suggesting utterance is 5 data (2.23%), inviting utterance is 7 data (3.13%) and 4 data (1.79%) of warning utterance. Whereas the results show that the types politeness strategies used is bald on record 132 data (59.20%), negative politeness 14 data (6.27%), positive politeness 69 data (30.94%) and off-record strategy 8 data (3.59%). The last is the language forms of directive utterances that show 201 data (90.13%) of imperative sentence, 16 data (7.17%) of interrogative sentence, and 6 data (2.70%) of declarative sentence. In the conclusion, there are the correlations among the intentions of directive utterances, the type of politeness utterances, and the language form of directive utterance in this research paper that 100% of commanding utterances that applying in the bald on record strategy are using imperative sentence.